Philosophy, Famine Relief, and the Skeptical Challenge From Disagreement. (30th October 2014) - Seipel, Peter
Abstract: Disagreement has been grist to the mills of sceptics throughout the history of philosophy. Recently, though, some philosophers have argued that widespread philosophical disagreement supports a broad scepticism about philosophy itself. In this paper, I argue that the task for sceptics of philosophy is considerably more complex than commonly thought. The mere fact that philosophical methods fail to generate true majority views is not enough to support the sceptical challenge from disagreement. To avoid demanding something that human reasoning cannot supply, sceptics must show that philosophers have sufficient overlap to resolve their disagreements in particular concrete cases.